COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN DESA WISATA BANTARAGUNG KABUPATEN MAJALENGKA - Nasywa Nur Hidayah; Satria Aji Imawan (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2026)
Community based tourism village development requires collaboration among multiple actors in management and decision-making processes. In practice, the involvement of government institutions, local communities, and supporting organizations often creates diverse patterns of cooperation shaped by the social context of each village. Bantaragung Tourism Village in Majalengka Regency represents one example of a tourism village that has developed through multi-actor involvement in managing village tourism activities. This study aims to understand the dynamics of Collaborative Governance in the development of Bantaragung Tourism Village by employing the Collaborative Governance model proposed by Ansell and Gash, which includes starting conditions, institutional design, facilitative leadership, and collaborative processes as an analytical framework. This research applies a descriptive qualitative method, with data collected through in depth interviews and documentation. The findings indicate that collaboration among actors comprising the Village Government, Tourism Awareness Group (Pokdarwis), Village Owned Enterprise (BUMDes), the Department of Tourism and Culture of Majalengka Regency, and the local community has been established through coordination, communication, and cooperative mechanisms in tourism village development. These interactions have gradually evolved through dialogue, role sharing, and community involvement in various tourism activities. Local leadership plays an important role in facilitating relationships among actors and maintaining collaborative continuity, although community participation in strategic decision making is still developing progressively. The study concludes that Collaborative Governance in the development of Bantaragung Tourism Village can be understood as a collaborative process formed through social interaction and shared experiences among actors, contributing to the sustainability of community-based tourism village management.